The Relationship between Knowledge and Nurse Compliance Regarding Preventing the Risk of Falls in Hospital Inpatient Rooms - Rahmah, Nur Miladiyah; Pratama, Muhamad Rizky; Minarningtyas, Asih (Universitas Prima Indonesia, 2024)
Patient safety is a fundamental healthcare principle recognized as a growing global public health challenge. The six goals of Patient Safety include accurate identification of patients, increased effective communication, increased safety of cautionary medicines, assurance of the correct surgical site, correct procedures and surgery on the proper patient, reduced risk of healthcare-associated infections, and decreased risk of patient injury due to falls. This fall incident resulted in damages and increased the length of treatment and patient care costs. Injured patients can require an extended hospital stay. This study aimed to determine the relationship between knowledge and nurses' compliance with preventing the risk of falls in patients at the West Java Regional Hospital, Bekasi City. This research method uses a cross-sectional approach to 54 nurses as a sample. The results of data analysis using the Chi-Square test showed a p-value of 0.153 (p<0.05). In conclusion, there is no relationship between nurses' knowledge and nurses' compliance regarding preventing the risk of falls in patients. Further research requires the observation of nurses' prevention of falls using the Morse fall scale observation sheets to determine whether nurses are obedient in their daily lives to prevent the risk of falls.